A case of beningn recurrent intrahepatic cholestasis - Dr.K. MADHUMIDHA; Dr.V.PADMA; Dr.R.KARTHIKEYAN (International Journal of Pharma and Bio Sciences, 2016)
Benign recurrent intrahepatic cholestasis (BRIC) is rare etiology of jaundice Around 70 cases have been reported since original description by Summerskill and Walshein1959. It is an autosomal recessive disorder, characterized by recurrent episodes of intense pruritus and jaundice that resolve spontaneously without leaving chronic liver damage. The attacks can start at any age, but the first attack is usually seen before the second decade of life. we report the case of young adult male patient of 30 years of age with BRIC who presented with recurrent cholestatic jaundice and pruritus with negative work up for all possible etiologies and a liver biopsy consistent with intrahepatic cholestasis. He improved on treatment with rifampicin and has not suffered another attack on flow up.